ANTECEDENTES EN ESPAÑA DE LA CRIMINOLOGÍA POSITIVA MODERNA Y DE LA CRIMINOLOGÍA CLINICA - Serrano Gómez, Alfonso (2020)
Criminology in Spain has been protected by criminalists. Some made theoretical contributions. At the end of the decade of the 1960s of the past century, a new stage was initiated with then appearance of the first empirical papers and those on clinical criminology. In recent years the Degree in Criminology has been created in more than thirty universities, although in the field of investigation we have few experts in the discipline. The scientific future of criminology in our country in the short term, even in the medium term, seems quite bleak.La Criminología en España ha sido tutelada por los penalistas. Algunos hicieron aportaciones teóricas. A finales de la década de los sesenta del siglo pasado se inicia una nueva etapa con la aparición de los primeros trabajos empíricos y de Criminología clínica. En los últimos años se ha creado el Grado en Criminología en más de treinta universidades, aunque en el campo de la investigación disponemos de pocos expertos en la disciplina. El futuro científico de la Criminología en nuestro país a corto plazo, e incluso a medio, parece poco prometedor.Criminology in Spain has been protected by criminalists. Some made theoretical contributions. At the end of the decade of the 1960s of the past century, a new stage was initiated with then appearance of the first empirical papers and those on clinical criminology. In recent years the Degree in Criminology has been created in more than thirty universities, although in the field of investigation we have few experts in the discipline. The scientific future of criminology in our country in the short term, even in the medium term, seems quite bleak